Milk intake enhances cerebral antioxidant (glutathione) concentration in older adults: A randomized controlled intervention study - Choi, In-Young; Taylor, Matthew K.; Lee, Phil; Alhayek, Sibelle Alwatchi; Bechtel, Misty; Hamilton-Reeves, Jill; Spaeth, Kendra; Adany, Peter; Sullivan, Debra K. (Frontiers in Nutrition, 2022)
Background: A major antioxidant, glutathione (GSH), is a key factor in the antioxidant defense mechanism against oxidative stress and aging-related functional declines. Our previous observational study showed positive correlations between brain GSH concentrations and dairy food consumption, particularly milk (p<0.001), in older adults. Objective: To investigate whether a recommended amount of milk intake (3 cups/day) in low dairy consumers enhances brain GSH concentrations through an intervention trial. Methods: Seventy-three older adults (60-89 years) with a low dairy intake (≤1.5 servings/day) were randomized (5:2 ratio) in this 3-month randomized clinical trial. The intervention group was provided 1% milk weekly and instructed to consume 3 cups of milk/day for three months while the control group continued their habitual intake of total dairy ≤1.5 servings/day (<1 cup of milk/day). Brain GSH concentrations were measured in the fronto-parietal region using our unique 3 T magnetic resonance chemical shift imaging technique at baseline and 3 months. Results: Among 73 randomized participants, 66 participants (49 intervention; 17 controls) completed the study. Milk intake in the intervention group increased from 0.2±0.3 cups/day to 3.0±0.6 cups/day (p<0.001) between baseline and the end of the study, while milk intake in the control group did not differ throughout the study duration (0.4±0.4 cups/day). The intervention group showed increases in brain GSH concentrations by 7.4±11.7% (p<0.001) in parietal and 4.7±9.8% (p=0.003) in fronto-parietal regions, and 4.6±8.7% (p<0.001) in overall brain concentration after the intervention compared with baseline, while the control group showed no changes. Conclusions: This study provides evidence that milk serves as a good dietary source to increase and/or restore brain GSH concentrations in older adults. Identifying dietary sources that effectively enhance antioxidant defenses and neuroprotection could lead to the development of new strategies to promote brain health in the aging population.